2021
DOI: 10.1158/1078-0432.ccr-21-0453
|View full text |Cite
|
Sign up to set email alerts
|

First-in-Human Study of the Biodistribution and Pharmacokinetics of 89Zr-CX-072, a Novel Immunopet Tracer Based on an Anti–PD-L1 Probody

Abstract: First-in-human study of the biodistribution and pharmacokinetics of 89Zr-CX-072, a novel immunopet tracer based on an anti-PD-L1 probody de Ruijter,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…human study results of novel immuno-PET radiotracers which target CD8 [25] and PD-L1 [26] in the tumour immune microenvironment. Given that PD biomarker studies of IO agents in early clinical development typically aim to demonstrate immunologic activity as proof-of-concept, it was not surprising that most PD assays involved quantification of immune cell subsets in the circulation and/or TME.…”
Section: Discussionmentioning
confidence: 99%
“…human study results of novel immuno-PET radiotracers which target CD8 [25] and PD-L1 [26] in the tumour immune microenvironment. Given that PD biomarker studies of IO agents in early clinical development typically aim to demonstrate immunologic activity as proof-of-concept, it was not surprising that most PD assays involved quantification of immune cell subsets in the circulation and/or TME.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, building on the encouraging preclinical data for 89 Zr-CX-072 highlighted above, Ruijter et al 108 recently reported on results of a sub study investigating this probody for immuno-PET in patients with metastatic cancer. PET images obtained 2 to 7 days after infusion of 89 Zr-CX-072 showed tumor uptake in all patients, even in those who were reported as PD-L1-negative by IHC.…”
Section: Article In Pressmentioning
confidence: 98%
“…Moreover, the maximum 89Zr-DFO-6E11 tumor-to-muscle ratio was associated with treatment response (p=0.025). Several early-phase clinical trials have confirmed the potential of immuno-PET targeting PD-L1 approaches for immunotherapy with different promising tracers 113–115 : the 89 Zr-atezolizumab, 98 the 89 Zr-CX-072, which is a PD-L1 targeting probody therapeutic, which is engineered to be activated in the tumor microenvironment by tumor-associated proteases, 114 and the 89 Zr-durvalumab. 115 …”
Section: Imaging To Increase Knowledge To Predict Responses and To Gu...mentioning
confidence: 99%